1994
DOI: 10.1002/j.2161-1920.1994.tb00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Personal and Career Counseling: A Challenge for Counselors

Abstract: In recent years career counseling has often been viewed as separate and distinct from personal counseling, ignoring a long tradition in the career development field that h a s consistently recognized the importance of personality factors in the process of choosing and maintaining a career. This paper argues for the use of an eclectic career counseling model that embraces both personality and career development theories. The model requires the counselor to be able to move back and forth between the active and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…Findings of this study are consistent with the findings of previous studies (e.g., Anderson & Niles, 1995;Dorn, 1992;Imbimbo, 1994;Krumboltz, 1993;Manuele-Adkins, 1992) which showed that counseling students hold misconceptions regarding interrelationships between career and personal counseling. Participants with no previous career counseling experience lacked a framework for understanding the purpose or value of career counseling.…”
Section: Discussionsupporting
confidence: 94%
“…Findings of this study are consistent with the findings of previous studies (e.g., Anderson & Niles, 1995;Dorn, 1992;Imbimbo, 1994;Krumboltz, 1993;Manuele-Adkins, 1992) which showed that counseling students hold misconceptions regarding interrelationships between career and personal counseling. Participants with no previous career counseling experience lacked a framework for understanding the purpose or value of career counseling.…”
Section: Discussionsupporting
confidence: 94%
“…Employment and career counselors should consider their role as a personal counselor as well as a career adviser. Imbimbo (1994) reported that distinguishing between career counseling and personal counseling disregards the reality that individuals have underlying issues that may interfere with career development (e.g., dealing with sexual orientation issues) and that a connection exists between one's work and one's life roles. Imbimbo also contended that each client will be different, and one may require short-term career guidance whereas another may need help dealing with self-esteem issues.…”
Section: Implications For Career Center and Employment Counselorsmentioning
confidence: 99%
“…Fortunately, there are accounts of case studies where career counselling interventions have positively resolved personal or psychological difficulties (e.g. Blustein, 1987; Imbibo, 1994; Lenz et al, 2010; Lucas, 1993; Super, 1993; Tolsma, 1993). This is not the most robust kind of evidence, as these are counsellors’ own narrative accounts.…”
Section: Direct Effectsmentioning
confidence: 99%